Impact of privatisation on state owned enterprises’ performance: case of COTCCO from 2000 to 2014 - Chiveto, Otilia T. (Midlands State University, 2017)
This paper is mainly focused on the impact of privatisation on state owned enterprises with specific reference to Cottco. Privatization leads to important changes in the nature and the structure of ownership of firms as well as in management personnel, which in turn significantly influence the performance of privatized firms. However the glory of the privatised cottco has been short-lived Cottco has been facing negative comments from the public within the borders of the nation. Poor performance, corruption, poor service delivery has become the order of the day to the extent that the organisation is almost closing as it now operating below its liquidation state. A number of methods were used including questioners and interviews so as to understand the causes. This study also finds that the competition resulted from the opening to foreign markets has significant and negative impact on the performance of privatized firms, the intended goals were not achieved and the welfare of the employees was undermined. Recommendations were given derived from the data that was collected.